Topological extraordinary optical transmission - BASKOURELOS, K.; O. Tsilipakos; Stefański, T.; S. F. Galata; Economou, E.; M. Kafesaki; K. L. Tsakmakidis (Phys. Rev. Research, 2022)
Τhe incumbent technology for bringing light to the nanoscale, the near-field scanning optical microscope, has notoriously small throughput efficiencies of the order of 104 −105, or less. We report on a broadband, topological, unidirectionally guiding structure, not requiring adiabatic tapering and, in principle, enabling near-perfect (∼100%) optical transmission through an unstructured single arbitrarily subdiffraction slit at its end. Specifically, for a slit width of just λeff/72 (λ0/138) the attained normalized transmission coefficient reaches a value of 1.52, while for a unidirectional-only (nontopological) device the normalized transmission through a λeff/21 (∼λ0/107) slit reaches 1.14; both limited only by inherent material losses, and with zero reflection from the slit. The associated, under ideal (ultralow-loss) conditions, near-perfect optical extraordinary transmission has implications, among diverse areas in wave physics and engineering, for high-efficiency, maximum-throughput nanoscopes and heat-assisted magnetic recording devices.